Coexistence of Ovarian Endometrioma, Leiomyoma, and Genital Tuberculosis Mimicking Malignancy: A Case Report - Kirana Paramitha Santosa; Anggar Jito (International Medical Journal Corp. Ltd, 2026)
Introduction: Genital tuberculosis (TB) can present with nonspecific symptoms and clinical findings that resemble gynecologic malignancy, particularly when accompanied by elevated tumor markers, large pelvic masses, and ascites.1 Case Report: A 34-year-old female presented with progressive lower abdominal pain for five months, especially during menstruation. Additional symptoms included weight loss, abdominal distension, difficulty with defecation and urination. Abdominal MSCT demonstrated the presence of ascites and a large adnexal mass compressing the rectum, suggestive of malignancy. Laboratory testing showed an elevated CA-125 level of 372.70 U/mL. Initially, ovarian malignancy was the primary differential diagnosis. After thorough consideration, a bilateral oophorectomy and hysterectomy were performed, despite the patient not yet having borne children. Histopathological examination of the surgical specimens revealed a leiomyoma, ovarian endometrioma, and chronic granulomatous inflammation consistent with TB infection was found in both ovaries and endometrium. Discussion: This case underlines the importance of considering genital TB in the differential diagnosis of pelvic masses with elevated CA-125, especially in TB-endemic regions.2 This is crucial because both diseases can coexist in the same individual. When malignancy is initially suspected, it is important to conduct a thorough investigation to rule out or confirm TB, as the treatment and management strategies differ significantly, potentially avoiding unnecessary aggressive intervention.3 Conclusion: This study emphasizes the importance of including GTB in the differential diagnosis of pelvic masses associated with elevated tumor markers, particularly in TB-endemic regions. This consideration is essential because benign pelvic masses and GTB may coexist in the same patient. Given the wide variability in clinical presentation and the limited accuracy of current diagnostic modalities, it may be misdiagnosed as a gynecologic malignancy which has a significantly different treatment strategies. Keywords: leiomyoma, endometrioma, genital tuberculosis